Microbiome role in pancreatic diseases development - Yu. V. Evsyutina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present the modern concept on the mechanisms of pancreatic disease development and role of intestinal and oral microbiome in pancreatitis pathogenesis. Summary. Intestinal barrier dysfunction, bacterial overgrowth syndrome and endotoxinemia are features of acute pancreatitis. Image-recognition systems (toll-like and NOD-like receptors) and microorganism-associated molecular patterns play important role in these processes. Obtained data indicate the presence of oral and gastrointestinal microbial changes at pancreatic diseases. Subsequently,Helicobacterpyloriinfection may play a role in development of autoimmune pancreatitis and pancreatic cancer,PorphyromonasgingivalisandAggregatibacteractinomycetemcomitans- in pancreatic cancer development. Conclusion. Original study results indicate the presence of oral and bowel microbial changes in pancreatic diseases. Taking into account the ability of probiotics to stimulate production of antimicrobial peptides, normalize epithelial barrier function, limit bacterial translocation, their the application may be promising for pancreatic diseases treatment.